Sebuah HUBUNGAN PENGETAHUAN, SIKAP, DAN PERILAKU PENGGUNAAN ALAT PELINDUNG DIRI PADA PERAWAT INSTALASI RAWAT INAP DENGAN KEJADIAN KECELAKAAN KERJA DI RSUD DR. H. ABDUL MOELOEK PROVINSI LAMPUNG - Amanah, Nur Suci; Utama, Winda Trijayanthi (CV. Jasa Sukses Abadi, 2024)
Nurses are often interacted with patients for a long time, thus nurses have a high enough risk factor. Therefore, Nurses need Personal Protective Equipment (PPE) to protect themselves from various potential hazards in the workplace and addition to prevent work accidents. This study aims to determine the relationship between knowledge, attitudes, and behavior of using PPE in inpatient nurses with the incidence of work accidents in RSUDAM Lampung Province. This study used an observational method with a cross sectional approach with a proportional random sampling technique. The research subjects were 158 RSUDAM inpatient installation nurses and the measuring instrument was a questionnaire. Data analysis was performed using Fisher's exact test. The results of this study showed a good level of knowledge as much as 81.6%, 50.6% positive attitude, 70.3% good behavior in the use of PPE. Meanwhile, the category of low incidence of work accidents was 93.7%. The results of statistical tests showed that there was a significant relationship between knowledge (p = 0.001), attitude (p = 0.001), and behavior (p = 0.001) using PPE with the incidence of work accidents. There is a relationship between knowledge, attitudes, and behavior of using PPE on inpatient installation nurses with work accident at RSUDAM Lampung Province.